Improving multiple exclusion homelessness (MEH) services: frontline worker responses to insecure attachment styles. Issue 6 (25th August 2021) - Theodorou, Nikoletta; Johnsen, Sarah; Watts, Beth; Burley, Adam
Abstract : Purpose: This study aims to examine the emotional and cognitive responses of frontline homelessness service support staff to the highly insecure attachment styles (AS) exhibited by people experiencing multiple exclusion homelessness (MEH), that is, a combination of homelessness and other forms of deep social exclusion. Design/methodology/approach: Focus groups were conducted with frontline staff (N = 19) in four homelessness support services in Scotland. Hypothetical case vignettes depicting four insecure AS (enmeshed, fearful, withdrawn and angry-dismissive) were used to facilitate discussions. Data is analysed thematically. Findings: Service users with AS characterised by high anxiety (enmeshed or fearful) often evoked feelings of compassion in staff. Their openness to accepting help led to more effective interactions between staff and service users. However, the high ambivalence and at times overdependence associated with these AS placed staff at risk of study-related stress and exhaustion. Avoidant service users (withdrawn or angry-dismissive) evoked feelings of frustration in staff. Their high need for self-reliance and defensive attitudes were experienced as hostile and dismissing. This often led to job dissatisfaction and acted as a barrier to staff engagement, leaving this group more likely to "fall through the net" of support. Originality/value: Existing literature describes challenges that support staff encounter when attempting to engage with people experiencing MEH, but provides little insight into the causes or consequences of "difficult" interactions. This study suggests that an attachment-informed approach to care can promote more constructive engagement between staff and service users in the homelessness sector.